The Effectiveness of Flipped Classroom Assisted by Microlearning Video on VLAN and Trunking Learning Outcomes in Vocational Schools - Ali Imran; Putri Ananda Sari; Rachmat M; Rahma; Risaldi; Rusna (Jurusan Teknik Informatika dan Komputer, 2024)
This study investigates the effectiveness of a flipped classroom model assisted by microlearning videos on students’ learning outcomes in VLAN and trunking topics in vocational schools. VLAN and trunking concepts are essential yet cognitively demanding networking competencies that require both conceptual understanding and procedural configuration skills. While flipped learning and microlearning have been widely studied, limited empirical evidence exists in vocational secondary networking education. This study addresses that gap by examining their combined impact on cognitive and practical performance. A quasi-experimental non-equivalent control group pre-test–post-test design was employed involving 64 Grade XI vocational students. The experimental group (n = 32) received flipped instruction supported by 5–8 minute microlearning videos, while the control group (n = 32) received conventional lecture-based instruction. Data were collected using a 30-item cognitive test and a performance-based practical skills rubric. Statistical analyses included independent and paired samples t-tests, normalized gain (N-gain), and Cohen’s d effect size. The experimental group achieved significantly higher post-test scores in cognitive outcomes (M = 84.38) compared to the control group (M = 72.19), t(62) = 6.58, p < 0.001. Practical skills scores were also significantly higher (86.72 vs. 74.53), t(62) = 7.46, p < 0.001. Normalized gain values were 0.60 (cognitive) and 0.68 (practical) in the experimental group, exceeding the control group (0.30 and 0.37). Large effect sizes were observed (d = 1.64 and d = 1.86). The quasi-experimental design and single-school context limit generalizability. Long-term retention was not examined. This study contributes empirical evidence supporting microlearning-enhanced flipped instruction in vocational networking education and provides a scalable model for competency-based technical training.